IMPLEMENTATION OF THE PROJECT FOR STRENGTHENING THE PROFILE OF PANCASILA STUDENTS AT ELEMENTARY SCHOOL OF CIANDAM AS AN EFFORT FOR SOCIO-CULTURAL CHANGE - Novianti, Nita; Marini, Arita; Zakiah, Linda (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
This research is motivated by the efforts made by the school to create students who have sustainable living behavior. Hopefully, this behavior will change the lifestyle of people who ignore waste. This research aims to analyze the implementation of the Strengthening Pancasila Student Profile (P5) Project activities with the theme Sustainable Lifestyle at the Elementary School of Ciandam, Sukabumi City as an effort to implement a positive culture which is hoped to have an impact on social and cultural change in society. This type of research uses descriptive qualitative methods. Data collection techniques include interviews, observation, and documentation. Data was collected through interviews with the school principal, deputy head of curriculum, teachers who taught in first grade, and six students. Observations were carried out directly during the implementation of P5 activities and analysis of post-P5 activity reports. Data were analyzed using six interrelated steps in the analysis of the interpretation of qualitative data as presented (Creswell, 2014). The research results show that 1) The stages of P5 activities consist of the stages of preparing the school ecosystem, designing P5, managing P5, processing assessments and reporting P5 results, evaluating and following up on P5; 2) Class I students participated in P5 activities with great enthusiasm; 3) The theme of a sustainable lifestyle has a positive impact on student behavior, especially towards waste; 4) Reporting on P5 activities is socialized at parent meetings as a follow-up form and is expected to bring about socio-cultural changes in society.